Post-Streptococcal Uveitis: A Narrative Literature Review - Gueorgui Markov; Yani Zdravkov; Alexander Oscar (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2023)
Streptococcus spp. are gram-positive bacteria and common human pathogens and commensals, causing diseases of various organs in children and adults. They are etiological factors of scarlet fever, pharyngitis, tonsillitis, pneumonia, endocarditis, erysipelas, impetigo, meningitis, necrotising fasciitis, and sepsis, among others. The post-streptococcal syndrome is a presumed autoimmune condition that has been associated with rheumatism, reactive arthritis, glomerulonephritis, and erythema nodosum. This literature review aimed to describe post-streptococcal uveitis in clinical practice. The onset of the immune-mediated complications has varied from 7 to 35 days post-infection. The ocular complications present mainly in the form of blepharoconjunctivitis. There are anecdotal case reports of episcleritis. Keratitis is another possible complication. Preseptal or orbital cellulitis has also been described. Uveitis has been a much rarer finding, and it is hypothesized that the pathogenesis is immune-mediated rather than due to intraocular bacterial infection. Post-streptococcal uveitis has been described in cases of both group A and group B infections. The onset of uveitis has been from 1 week to 36 months after the infection. Post-streptococcal presents mostly as nongranulomatous, bilateral anterior uveitis with a good prognosis and affects mostly young people. Nevertheless, all anatomic types of intraocular inflammation have been observed. The common denominators between the varying clinical pictures appear to be the history of streptococcal infection, most frequently pharyngitis, an elevated anti-streptolysin O titer, and in the more recent studies-the raised anti-deoxyribonuclease antibodies. Furthermore, there has been a generally good therapeutic response to corticosteroids. Few cases have required immunomodulation with methotrexate, mycophenolate, and adalimumab.